PENGARUH TERAPI REMINISCENCE TERHADAP TINGKAT DEPRESI PADA LANSIA (LITERATURE REVIEW): Pengaruh Terapi Reminiscence Terhadap Tingkat Depresi Pada Lansia (Literature Review) - Hastuti, Hera Hastuti; Giyanti, Ummi (Ruang Ide Publisher, 2022)
The country of Indonesia is currently heading toward an aging population (an old country), with the number of elderly people increasing from year to year. Along with increasing age there are functional changes in the body of the elderly, including neurological function. The most common mental and neurological disorders in this age group are dementia and depression which affect the world’s elderly respectively. Depression is usually treated through long-term medications. Reminiscence therapy is specifically recommended for older people with depression. The purpose of the literature review is to find out more about the effect of reminiscence therapy on the level of depression in the elderly. The method used is by searching articles through databases such as Google scholar, Pubmed, and Researchgate Journal with the keywords “Elderly” AND “Reminiscence Therapy” AND “Depression”. The search results from the three databases obtained 18,254 articles which were then screened, obtained 6 journals that match the PICOT inclusion criteria, problems, and research objectives. In general, the six journals state that significant reminiscence therapy can reduce the level of depression in the elderly, resulting in a decrease in the TGDS value to a mean of 7.09 points. The therapy is carried out by telling stories about their memories, making the elderly interact with other elderly and expressing themselves which can reduce depression in the elderly. Therapy is carried out in 6-16 sessions or 8 weeks. It is expected that elderly nurses can plan the use of reminiscence therapy to prevent and overcome the problem of depression in the elderly. Keywords: Depression; Elderly; Memory; Reminiscence Therapy